What Is the Role of Deep Learning in Radiology Diagnosis? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2018)
Artificial Intelligence (AI), and its subfield of deep learning (DL), is rapidly transforming various industries, with healthcare being one of the most promi...
Keywords: AI in Medical Imaging and Diagnostics; Learning; Radiology; Diagnosis; Artificial Intelligence; Machine Learning; Deep Learning